Exploring mood and anxiety disturbances across Ramadan: a comparative study of Saudi medical students before, during, and after fasting - Lone, Ayoob; Hadadi, Abdulaziz Shary; Alnawah, Ahmed Khalid; Alshammary, Alya Abdualrahman; Almutairi, Razan Manei; Ali, Sayed Ibrahim; Abid, Naushad (Frontiers in Psychology, 2025)
Ramadan intermittent fasting (RIF) is a form of diurnal intermittent fasting observed by Muslims worldwide during the month of Ramadan. Previous studies have highlighted various benefits of RIF, particularly in healthy individuals, with positive effects on mood. Despite the physiological demands of RIF, limited research exists on its psychological implications for medical students—a population under considerable academic stress. This study examines changes in the mood of medical students during RIF and explores how these changes may vary according to demographic factors. This prospective study involved 108 medical students who completed the Brunel Mood Scale and demographic questionnaire at three distinct intervals: 1 week before, during, and 1 week after Ramadan. Data was analyzed by repeated measures analysis of variance. The Wilks’ Lambda test was employed to compare the means and evaluate the significant effects of RIF on mood. Statistical significance was set at p < 0.05. The findings of this study revealed significant changes in mood during Ramadan. While anger levels remained relatively stable across all three-time points, with only a slight increase during fasting. In contrast, confusion and depression gradually declined, suggesting improved emotional well-being as Ramadan progressed, particularly after fasting ended. Fatigue and tension were highest during the fasting period, indicating greater physical and emotional strain. Meanwhile, vigor temporarily decreased during fasting but returned to higher levels afterward. Result of analysis of variance identified tension as the most significantly affected emotional state (p = 0.03). The analysis of emotional states across demographics highlights key significant relationships, with tension showed the strongest associations among the mood dimensions and was significantly affected by academic year (p < 0.01) and smoking status (p = 0.04). Fatigue showed significant effects across multiple demographics, including area of residence (p = 0.03), family structure (p = 0.01), sex (p = 0.04), income (p = 0.02), and smoking status (p = 0.01). Confusion was significantly influenced by academic year (p = 0.01), while depression showed significant relationships with income (p = 0.03) and smoking status (p = 0.04). These findings suggest that tension, fatigue, and confusion are particularly sensitive to demographic variations. The study highlights the complex relationship between RIF, emotional outcomes, and sociodemographic variables in medical students, underscoring the need for tailored interventions to support students’ well-being during fasting periods. These findings provide valuable insights into the psychological impact of fasting in the context of medical education.